Polygamy in Pesantren Community: Analysis of the Novel Dua Barista by Najhaty Sharma - hasan, khanifil istantina hasan; Senja Salsa Kahfila1,; NurJihan Najwa Fitriyah,; Zulfi Zumala Dwi Andriani, (ELite Journal : International Journal of Education, Language and Literature, 2025)
This study examines the interaction between feminism and polygamy within the pesantren (Islamic boarding school) environment through an analysis of Najhaty Sharma's novel Dua Barista. The novel explores the lives of women in pesantren, particularly in confronting the realities of polygamy. Using a feminist approach, this research delves into how the female characters in the novel respond to and challenge patriarchal norms that uphold polygamy. Additionally, this study highlights how pesantren, as traditional Islamic institutions, provide a social and religious framework that shapes gender dynamics. The findings reveal that Dua Barista not only critiques the practice of polygamy but also portrays women's struggles to achieve justice and equality in a space often dominated by men. This article contributes to the discourse on gender, religion, and literature in Indonesia.